PENDIDIKAN INDONESIA:DARI HEGEMONI DAN KUASA PENGETAHUAN KE PENDANGKALAN KEMANUSIAAN - Iskandar Zulkarnain, S.IP., M.A, - (Universitas Bangka Belitung, 2013)
This Â article Â discusses Â about Â hegemony Â and Â knowledge Â power Â (the Â authorities) Â which created Â less Â humanization Â in Â Indonesian education. Â This Â study Â uses Â IPS Â (social Â studies subject matter) as the object of the study. The result of the study shows three causes of less humanization Â in Â social Â sciences Â (IPS), Â namely: Â the Â first, Â the Â historical Â background Â of Indonesia Â is Â full Â of Â political Â and Â in Â doctrinal Â nuance. Â So Â the Â orientation Â of Â Indonesian education Â is Â automatically Â reduced Â for Â the Â authorityâs Â interests. Â Second, Â the implementation Â of Â IPS Â teaching Â learning Â model Â is Â not Â flexible. Â It Â is Â monotones Â and homogeny. Â It Â is Â creates Â less Â critical Â thinking Â among Â students. Â The Â thirst, Â there Â was Â a symbolical violence in our education because of authorities superiority (teachers, schools) on students.Keyword :Â Education, Hegemony, and Dehumanization